PENDAMPINGAN KOMPETENSI PETUGAS DALAM IMPLEMENTASI REKAM MEDIS ELEKTRONIK (RME) DI PUSKESMAS PERUMNAS UTARA - Budiyanti, Nita (Fakultas Teknologi Informasi dan Industri Unisbank, 2025)
Electronic Medical Records (EMR) is a challenge that must be met in the era of digital transformation in the health sector. The implementation of EMR has a positive impact on recording administrative and clinical information to be more efficient and effective. The presence of EMR in addition to providing benefits is also faced with several challenges related to the protection of sensitive patient data. This community service aims to improve the competence of officers at the North Perumnas Health Center regarding data security principles including confidentiality, integrity and availability which have been regulated in the Minister of Health Regulation Number 24 of 2022 concerning Medical Records. The method used was mentoring 8 participants, with evaluation through pre-test and post-test. The results showed an increase in the average score from 74.87 to 84.25 with a difference of 9.37 points or an increase of 12.5%. Based on these results, it is clear that the mentoring provided has a positive impact on developing the competence of officers regarding the data security aspect in EMR management.